Answer:
kinetic energy of charge will be [tex](1/k)*(2Q^2/3d)[/tex]
Explanation:
First calculate the initial potential energy of each charge;
PE1=[tex](1/k)*(Q^2/d)[/tex];
When the charges are at distance of 3d then its potential energy is;
PE2=[tex](1/k)*(Q^2/3d)[/tex];
And kinetic energy is equal to difference between their potential energy at two different positions,
So,
K.E=PE1-PE2;
K.E=[tex](1/k)*(Q^2/d)-(1/k)*(Q^2/3d)[/tex];
K.E=[tex](1/k)*(2Q^2/3d)[/tex];
Hence the kinetic energy of charge will be [tex](1/k)*(2Q^2/3d)[/tex]